Fulvia fulva [syn. Cladosporium fulvum, Passalora fulva] races in Argentina are evolving through genetic changes and carry polymorphic avr and ecp gene sequences - Lucentini, César Gustavo (2021)
The aim of this work was to study further the population of Fulvia fulva [syn. Cladosporium fulvum, Passalora fulva] in Argentina particularly in terms of diversity at the genetic level by means of ISSR. Also, we studied polymorphisms within avr and ecp sequences, what incidentally might lead to the development of new races. Argentinian tomato cultivars only are affected by two races of F. fulva and the data we provide here indicates that the populations of these two races are under an evolutionary process. Representatives of them had several polymorphisms within the coding sequences of effectors, but they are not constrained to avr genes, probably because, based on field data, resistant cultivars are not available. Most polymorphisms observed in avr and ecp genes were deletions or insertions (INDELs) or single nucleotide polymorphisms (SNPs). Therefore, probably the environment and management practices are the most important factors driving evolution of these races in Argentina and this might explain why the pathogen population is not driven at the pathogenic or race level.